STRATEGI PEMBELAJARAN BAHASA ARAB BERBASIS KEBAHASAAN AL-QUR’AN - Syah, Safaruddin; Safitri, Citra Dwi (Al Hikmah: Jurnal Tarbiyah dan Ilmu Keguruan, 2025)
Arabic language plays a vital role in the life of Muslims as the language of the Qur’an. A deep understanding of the Qur’an requires comprehensive mastery of Arabic, encompassing meaning, structure, and linguistic context. This study aims to examine the urgency of Arabic learning based on Qur’anic linguistics, its strategies and implementation in language instruction, as well as its benefits for developing linguistic competence and spiritual understanding. The research employs a library-based method, with data collected from relevant sources such as books and recent scholarly journals. The findings reveal that Qur’an-based Arabic learning emphasizes mastery of vocabulary and sentence structures found in the Qur’an, enabling students to comprehend meanings and contexts more profoundly. This approach also enriches learners’ understanding of Arabic culture and creates opportunities for the development of linguistic corpus, which in turn contribute to research and development in the field of Arabic linguistics.